YOGA ASANAS: LIFESTYLE KESEHATAN DI MASA NEW NORMAL - Subrata, I Nyoman (JURNAL YOGA DAN KESEHATAN, 2020)
This research examines the application of yoga asanas in a new level of life (new normal) during the Covid-19 virus pandemic. The discourse about the Covid-19 outbreak directs humans to be able to live healthy lives. Health is an important benchmark in the transition period to keep the body healthy during activities. Within this framework, this study uses a qualitative descriptive research method that is described using a socio-religious approach. Due to the phenomenon that occurs in society, activities that are rarely outside the home make a healthy lifestyle so important. A healthy lifestyle by applying the practice of yoga asanas during work from home is a choice for some people to make rhythm adjustments in activities in a productive way and balanced with nutritious food and drinks. Yoga asanas in physical distancing situations certainly have many benefits to support body health. Not only as a lifestyle or a healthy lifestyle, but yoga asanas has now become the most important part of implementing the natural health of the human body to increase immunity, maintain body stability, increase concentration, control thoughts, prevent depression, and even reduce stress management in the current new normal.Â